Hybris - nemesis - balance. Problemer med genbrug af ordbogsdata set fra Den Danske Ordbog - Hjorth, Ebba (Nordiske Studier i Leksikografi, 1997)
According to the original plans, The Danish Dictionary (DDO) was to build upon already existing machine-readable dictionary data as well as make use of quotations from a machinereadable corpus, which had been compiled by The Danish Dictionary and consists of 40 million running words. However, when the machine-readable dictionary data was compared with the language usage in the large text corpus, the original plans had to be revised and the intention of re-using existing dictionary data was abandoned. The choice of words as well as the orthographic, morphological, semantic and syntactic descriptions had to be revised radically in order to make the language coverage more adequate. The dictionary had hereby changed status from being a corpus-backed dictionary to being a corpus-based dictionary.